2010
DOI: 10.1590/s1413-86702010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of cerebral toxoplasmosis: comparing markers that determine Toxoplasma gondii by PCR in peripheral blood from HIV-infected patients

Abstract: As cerebral toxoplasmosis is the most common cerebral focal lesion in AIDS patients, this study evaluated three PCR markers for diagnosis, since some limitations remain present, such as low parasite levels in some clinical samples. The molecular markers were B22-B23 and Tg1-Tg2 (based on the B1 gene) and Tox4-Tox5 (non-coding fragment, repeated 200-300-fold). DNA samples from 102 AIDS patients with previously known diagnosis were analyzed. The cerebral toxoplasmosis group was constituted of DNA extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…PCR in peripheral blood is currently used with immunocompromised patients for the diagnosis of cerebral (especially in HIVpositive patients) or disseminated toxoplasmosis. It yields good sensitivity (between 89.3% and 95.5% in a study by Mesquita et al [13]), although this is dependent on the marker that is used. The volume of the sample used for DNA extraction is thought to be of great importance also (see below).…”
Section: Discussionmentioning
confidence: 99%
“…PCR in peripheral blood is currently used with immunocompromised patients for the diagnosis of cerebral (especially in HIVpositive patients) or disseminated toxoplasmosis. It yields good sensitivity (between 89.3% and 95.5% in a study by Mesquita et al [13]), although this is dependent on the marker that is used. The volume of the sample used for DNA extraction is thought to be of great importance also (see below).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the PCR sensitivity, the CSF samples should be processed rapidly within 48 h of collection to prevent Taq polymerase inhibition that could modify PCR results. 26 In addition, the DNA extraction and PCR inhibitors may be evaluated by a primer set that amplified human PCR fragments. In this study, positive amplifications showed that no substance present in DNA samples inhibited the reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of the AIDS epidemic, diagnosis of cerebral toxoplasmosis was confirmed at autopsy (Table S5, online version only) or by needle biopsy of lesions suspected by computer tomography (CT) scan. Currently, diagnosis is aided by attempts to demonstrate live T. gondii parasites, antibodies to T. gondii or T. gondii antigens or T. gondii DNA in blood or CSF or even in saliva (Borges and Figueiredo, 2004; Vidal et al 2004; Colombo et al 2005; Meira et al 2008; Nogui et al 2009; Correia et al 2010; Mesquita et al 2010 a , b ; Meira et al 2011). Obviously, use of peripheral blood for diagnosis is less invasive and good results were obtained using quantitative serology and DNA detection in cerebral toxoplasmosis (Vidal et al 2011).…”
Section: Toxoplasmosis In Humansmentioning
confidence: 99%